Physicochemical properties of new cellulosic fiber extracted from Carica papaya bark. Issue 2 (17th February 2019) - Saravana Kumaar, A; Senthilkumar, A; Sornakumar, T; Saravanakumar, S.S; Arthanariesewaran, V.P
ABSTRACT: This article presents the characteristics of Carica papaya fibers (CPFs) extracted from the bark of the perennial papaya plant. Detailed chemical compositions of CPFs such as cellulose, lignin, ash, moisture, and wax contents were established and determined by using standard methods. Further, chemical groups, crystalline structure, surface roughness, and thermal stability of CPFs were examined using Fourier transform infrared analysis, X-ray diffraction, atomic force microscope, and thermogravimetric analysis, respectively. The physico-chemical properties of CPFs, crystallinity index (56.34%), cellulose content (38.71 wt. %), hemicellulose (11.8%), and density (943 kg/m 3 ) were compared to those properties of other natural fibers. The results suggest that the biodegradable CPFs can be used as a potential reinforcemnet in the polymer matrix composite structure.